Non-invasive bunch length diagnostics based on interferometry from double diffraction radiation target - Shkitov D. A. Dmitriy Andreevich; Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Shevelev M. V. Mihail Viktorovich; Zhang J. B.; Lu S. L.; Yu T. M.; Deng H. X. (2013, 2013)
Заглавие с экрана